P22 The relationship between social deprivation and hospital admissions with acute exacerbation of chronic obstructive pulmonary disease (AECOPD). (14th November 2013) - Grecian, RJ; Grecian, SM; Wright, J; Balata, H; Ashish, A; Aziz, I
Abstract : Background: AECOPD is a major source of hospital admissions. Research is underway to reduce such admissions, but the effect of social deprivation on AECOPD hospital admissions and length of stay is unknown. Aims and Objectives: To analyse the effect of social deprivation on hospital admissions and length of stay in AECOPD. Methods: Retrospective review of hospitalisation with a primary diagnosis of AECOPD Sep 11–Aug 12 in a UK hospital. Patients were assigned an index of multiple deprivation score based on postcode and subdivided into quintiles. For each quintile, total admissions and median length of stay per admission were calculated and corrected for population size (per 100, 000 residents). Fisher's exact test (two-tailed) was used to compare quintiles. The least deprived quintile represented <5% of the population and was excluded. Results: There were significantly higher numbers of hospital admissions in patients from more deprived postcodes as compared to affluent areas (p < 0.001). There was no significant difference in median length of stay between quintiles (Table 1 ). Conclusions: Patients from socio-economically deprived backgrounds have higher rates of hospital admissions with AECOPD. Deprivation does not influence length of stay; this could be due to a dedicated COPD unit. Increasing healthcare investment in deprived areas should be considered.